Cross Jurisdictional Boundaries to Build a Health Coalition: A Kentucky Case Study - Carman, Angela L.; McGladrey, Margaret L. (Frontiers in Public Health, 2018)
Cross-jurisdictional sharing is accomplished through collaboration across jurisdictional boundaries to deliver essential public health services and solve problems that cannot be easily addressed by single organizations or jurisdictions. Partners across 10 counties and three public health jurisdictions of the Barren River Area Development District (BRADD) convened as Barren River Initiative to Get Healthy Together (BRIGHT), a community health improvement coalition. Focus groups and interviews with BRIGHT members indicate that the use of effective strategies to focus collaborative health improvement efforts fosters a cohesive coalition even when the group is populated by individuals from across public health jurisdictional boundaries. Focusing strategies identified included: the importance of organizing workgroups so members can draw upon expertise, adoption of a community engagement model for health assessment and improvement; and use of a facilitator, who offers guidance and administrative support to groups and focuses members on accomplishing goals.